PENERAPAN SANKSI TERHADAP PELANGGARAN LALU LINTAS PADA MODIFIKASI KENDARAAN BERMOTOR YANG DILAKUKAN OLEH PENYEDIA JASA BECAK ODONG-ODONG DI KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Currently the rules for traffic using motorized vehicles and motorized vehicle modifications in Indonesia have been regulated based on Law Number 22 of 2009 concerning Road Traffic and Transportation. Based on the aforementioned statutory regulations, what is called a vehicle or transportation is a vehicle for means of transportation, either driven by machines or by living things. Furthermore, Traffic is the movement of vehicles and road traffic spaces. whereas roads are infrastructure designated for moving transport.This type of research can be classified in the type of sociological legal research (empirical), because in this study the author directly conducts research on the location or place under study in order to provide a complete and clear picture of the problem being studied. This research was conducted at the Riau Regional Police, while the population and sample were the Head of Traffic Division of the Pekanbaru City Transportation Service, members of the Pekanbaru City Transportation Service and Odong-Odong Service Providers.The conclusions that can be obtained from the results of the research are First, the application of sanctions for traffic violations on motorized vehicle modifications carried out by odong-odong motorized pedicab service providers if each party who wishes to modify their motorized vehicle is required to have a permit for the modification as required in Law No.22 of 2009 and Government Regulation No.55 of 2012 concerning Vehicles. Second, obstacles and efforts in the application of traffic prohibition sanctions on motorized vehicle modifications carried out by odong-odong motorized pedicab service providers in Pekanbaru in several ways, namely First, conducting regular outreach on road use properly and correctly in accordance with statutory regulations. - applicable legislation. Second, conducting raids on the equipment of motorized vehicles that are not suitable for feasibility (modification). Third, tighten the requirements for obtaining a driver's license.Keywords: Traffic, Sanctions, Violations, Motor Vehicles, Modifications.